1974
DOI: 10.1037/h0036861
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cue function of olfactory stimulation in mice with septal lesions.

Abstract: Normal mice and mice with septal lesions were trained on a go/no-go discrimination task (multiple fixed interval of 15 sec., 15-seo. extinction schedule). When the discriminative stimulus (the one which indicated to the subject whether responding at the end of the interval would be reinforced) was a pellet of food (delivered at the start of the interval) or odor of food or non-nutritive substance (present throughout the 15-sec. interval), acquisition of septum-damaged mice was enhanced. These lesions did not, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A considerable amount of evidence now suggests that septal lesions affect a variety of behaviors by enhancing the appetitive value of food reinforcement. This hypothesis has been used to account for enhancement following septal lesions in the performance of two-lever alternation (Carlson & Cole, 1970), go-no-go alternation (Carlson & Norman, 1971), runway alternation (Carlson et al, 1972), and discrimination tasks cued by presence or absence of a food pellet (Carlson et al, 1972;Carlson & Vallante, 1974). The present study further suggests that increased appetitive value of food might at least partially acount for the DHL deficit and retarded extinction of a food-motivated task following septal lesions.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…A considerable amount of evidence now suggests that septal lesions affect a variety of behaviors by enhancing the appetitive value of food reinforcement. This hypothesis has been used to account for enhancement following septal lesions in the performance of two-lever alternation (Carlson & Cole, 1970), go-no-go alternation (Carlson & Norman, 1971), runway alternation (Carlson et al, 1972), and discrimination tasks cued by presence or absence of a food pellet (Carlson et al, 1972;Carlson & Vallante, 1974). The present study further suggests that increased appetitive value of food might at least partially acount for the DHL deficit and retarded extinction of a food-motivated task following septal lesions.…”
Section: Discussionmentioning
confidence: 51%
“…The nature of the mechanism disrupted by septal lesions, which produces this alteration in responsiveness toward food reinforcement, is not yet clear. Carlson and Vallante (1974) observed that septal lesions enhance reactivity to olfactory stimuli in general. It is possible that septal lesions increase sensitivity to chemical stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicated that the act of not responding was critical to the problems encountered and illustrated the inhibitory role of the septum in normal behavior. Interestingly, enhanced performance on alternation and go-no-go tasks have been described in several experiments (e.g., Carlson & Cole, 1970;Carlson & Norman, 1971;Carlson & Vallante, 1974), suggesting that the relationship between attentional performance and septal damage is complex and task-dependent.…”
Section: Septal Influencesmentioning
confidence: 91%
“…Additional evidence for the functional relatedness of the areas comes from several recent studies demonstrating changes in olfactory sensitivity after septal damage (Carlson & Vallante, 1974;Kemble & Nagel, 1975;Vom Saal, Hamilton, & Gandelman, 1975). For example, Vom Saal et al found that rats with septal damage acquired an olfactory discrimination more rapidly than normals.…”
mentioning
confidence: 90%